Clinical Performance of Three Silicone Hydrogel Daily Disposable Lenses. Issue 3 (March 2015) - Varikooty, Jalaiah; Schulze, Marc M.; Dumbleton, Kathy; Keir, Nancy; Woods, Craig A.; Fonn, Desmond; Jones, Lyndon W.
ABSTRACT: Purpose: To determine the clinical performance of DAILIES TOTAL1 (DT1), Clariti 1Day (C1D), and 1-DAY ACUVUE TruEye (AVTE) silicone hydrogel daily disposable contact lenses (SiHy DDCLs). Methods: Eligible participants, subdivided into asymptomatic and symptomatic groups, wore each SiHy DDCLs for three consecutive days. Each participant attended three visits (on day 1 at 0 hours; on days 1 and 3 after 8 hours of wear) per lens type. The order of lens wear was randomized, with at least 1 day washout between lenses. Lens-related performance was evaluated by assessing lens surface deposits, wettability, pre-lens noninvasive tear breakup time, lens movement, and centration; ocular response assessments included conjunctival redness, corneal staining, and conjunctival staining and indentation. Results: Fifty-one asymptomatic and 53 symptomatic participants completed the study. For all visits, the mean noninvasive tear breakup time was about 1 second longer with DT1 than with C1D and AVTE (p < 0.01). Overall, the wettability of all three lenses was good; however, DT1 was graded marginally better than the other lenses (both p < 0.01). On day 3, eyes wearing AVTE had significantly more dehydration-induced corneal staining compared with DT1 (AVTE, 24%; DT1, 11%; p < 0.01). After 8 hours, conjunctival staining was different between lenses (greatest with C1D and least with DT1; all p < 0.01). Conjunctival indentation was more prevalent with the C1D lenses (n = 70) compared with DT1 (n = 1; p < 0.01) and AVTE (n = 11; p < 0.01). There were no differences between asymptomatic and symptomatic lens wearers for any of the clinical parameters (all p > 0.05). Conclusions: Each of the three SiHy DDCLs performed well. Noninvasive tear breakup time was longest and wettability was greater with DT1. C1D had the most conjunctival staining conjunctival indentation. There was no difference between asymptomatic and symptomatic wearers with regard to ocular response and contact lens–related parameters. These results suggest that SiHy DDCLs may be an excellent contact lens modality for the symptomatic patient.